Age Differences and Working Memory Performance - Anis, Maliki (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study aimed of this research was to investigate into age differences in working memory performance, specifically verbal working memory performance based on total correct items recalled and total time taken. This study included thirty (30) participants, including Malaysian students and undergraduate students at the University Malaysia Sarawak (UNIMAS). A quasi-experimental design was used in this work to conduct quantitative research. The Pearson correlation, Mann Whitney u-test and Independent t-test were then employed to test the study's hypotheses. The findings revealed that a significant age difference was detected in terms of verbal working memory performance based on the total correct items recalled, with young adults outperforming adolescents in the task. In terms of the time it took for participants to answer, the results demonstrated that there was no significant difference between age and age groups on verbal working memory performance based on total time taken, as previous research had revealed. This study also discussed the implications of the findings for future researchers to consider.